SYNTHESIS AND CHARACTERIZATION OF FLUOROPHORE-BASED CARBON DOTS FROM MEDICINAL PLANTS FOR BIOIMAGING APPLICATION - Dwi Annisa, Windy
Fluorophores of medicinal plants-based carbon dots have been synthesized from chlorophyll in sambiloto leaves (Andrographis paniculate) and curcumin in turmeric as carbon sources. A few problems such as low solubility in water, bad photostability, and high toxicity of fluorophore are limitations that could be solved by a modification to CDs. Controlling the particle size or functional group modification on the surface will affect the photoluminescence characteristic utilized as a bioimaging agent which is more compatible with the human body. Moreover, the small size of particles that only range from 1 to 10 nm can penetrate through the cell membrane to the target site. Carbon dots based on natural sources enable the application in nanomedicine as theranostic since its lower toxicity, biocompatible, and sustainable properties. In this study, the synthesis of CDs was carried out by bottom-up approach using the hydrothermal method at a certain temperature and duration with the variation of nitrogen doping using urea. After the purification process, the colloid of CDs with blue luminescence and uniform size was obtained due to controlled temperature and pressure so that the energy was enough to form the structure of CDs. IR spectrum of reaction product compared to EAP and curcumin showed few alterations, such as the reduction of the ester functional group to be ether forming core of CDs, forming conjugated-double bond by the shifting of double bond carbon wavenumber, and the higher intensity of hydroxyl/amine. CDs showed good stability in the physiological condition of the body with neutral pH and the presence of ionic solution which is compatible with in vitro assay to HDF cells. The doping of nitrogen by adding urea showed an alteration of surface charge which is more positive based on zeta potential measurement. As the more positive CD particles formed, where AP CDs, APU CDs, Cur CDs, and Cur-U CDs have charges of -11.8, -2.5, -37.7, and -16,5 mV, respectively, showed that APU CDs were the best particle to penetrate cells than others related to the alteration of the surface charge and the functional group contained in the CDs.